2015
DOI: 10.1038/srep16905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on fluoride metabolism in adult humans: a pilot study

Abstract: An understanding of all aspects of fluoride metabolism is critical to identify its biological effects and avoid fluoride toxicity in humans. Fluoride metabolism and subsequently its body retention may be affected by physiological responses to acute exercise. This pilot study investigated the effect of exercise on plasma fluoride concentration, urinary fluoride excretion and fluoride renal clearance following no exercise and three exercise intensity conditions in nine healthy adults after taking a 1-mg Fluoride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…Physical activity/sedentary behaviour and/or skeletal development stage impacts DUFE, with renal clearance of F declining with increasing physical activity . A recent study in South Africa, reported an increase in activity level with age; with 9‐11 year‐old boys and 12‐14 year‐old girls more physically and aerobically active than boys and girls aged 5‐6 years .…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity/sedentary behaviour and/or skeletal development stage impacts DUFE, with renal clearance of F declining with increasing physical activity . A recent study in South Africa, reported an increase in activity level with age; with 9‐11 year‐old boys and 12‐14 year‐old girls more physically and aerobically active than boys and girls aged 5‐6 years .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zohoori et al (2015) measured fasting ionic F levels in nine healthy adults aged 20–35 years (5 men and 4 women) residing in a nonfluoridated community in the UK [218]. The mean baseline ionic plasma F level was reported to be 3.2  μ mol/l.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed in our previous studies, which were performed on a similar experimental model, that long-term fluoride exposure of rats did not produce any changes in the fluoride concentration in the serum, probably because of high urinary removal [19]; however, accumulation of this element was observed in some brain structures [20]. Thus, fluoride may act as a neurotoxic agent despite its low level in serum.…”
Section: Discussionmentioning
confidence: 67%